Biodegradation of organic compounds and decrease in electrical conductivity by native consortium in effluents from the olive industry - Mariela Maldonado; Mario Baigori; Graciela Affranchino (International Journal of Recycling of Organic Waste in Agriculture)
Purpose Effluents from machined olive waters are highly polluting. These have high organic load values such as the biological demand of oxygen and the chemical demand of oxygen, salinity, and others, which far exceed current regulations. The objective of this work was to achieve, through bioremediation by native microorganisms, the reduction of effluent contamination.Method Bioremediation was achieved by supplementing the effluent with a source of carbon, nitrogen, and phosphorus in the approximate ratio 100: 5: 1, under aerobic conditions at room temperature (25 ± 1 °C) for a period of 7 to 14 days.Results The consortium of microorganisms (bacteria and yeasts) was identified as: Pseudomonas aeruginosa strain Kasamber 11, Pseudomonas aeruginosa strain 1816, Klebsiella sp. strain DE004, Enterobacter sp. DKU NT 01, Pseudomonas sp. KC31, Bacillus sp. MG06, Candida thaimueangensis NWP2-1, Klebsiella sp. SI-AL-1B, Bacillus pumilus strain LX11, Bacillus sp. B9 (2015b), Bacillus pumilus strain Y7, Planomicrobium sp. strain MSSA-10 16S, Candida thaimueangensis strain S04-2.2 and one microorganism without identification. A reduction of approximately 40-80% of specific parameters and contamination indicators such as biological oxygen demand (BOD5), chemical oxygen demand (COD) and electrical conductivity was achieved.Conclusion The microbial consortium achieved the reduction of the original contamination of the effluent from "mechanized olives" by biostimulation, transforming it into a less contaminated liquid that could be used for other uses or destinations.